Impact of Trade Facilitation on the Freight Forwarding Industry: A Case of Plumtree Border Post - Wilford Mawanza; Mellisa Z.L Ncube; Blessed Mpofu (International Journal of Supply Chain Management, 2018)
The main aim of the study was to investigate the impact of trade facilitation in the freight forwarding industry. The study was largely prompted by the high levels of delays that are experienced at border posts by traders and tourists, hence the need to investigate the challenges faced by freight forwarders resulting in delays and the effectiveness of the Plumtree border post as a trade facilitation tool. The study focused on the challenges, causes and effects of different trade facilitating agencies that directly affect the freight forwarding industry through a case survey of 72 respondents comprising freight forwarders, clearing agents, traders and customs officers at the Plumtree border post was used. The results revealed that there is greater need to increase transparency and integrity in the administration of daily operations at the border post. There are increased direct and indirect costs such as transport and customs documentation leading to inefficiency, increased lead time and fraudulent activities arising amongst freight forwarders and clearance delays for consignments hence it was recommended that the freight forwarding industry should propose to trade facilitation agencies to fully adopt and implement trade facilitation standards, recommendations and best practices which have been developed by various international bodies.